Cell‐free eukaryotic systems for the production, engineering, and modification of scFv antibody fragments. Issue 4 (July 2014) - Stech, Marlitt; Hust, Michael; Schulze, Corina; Dübel, Stefan; Kubick, Stefan
<x xml:space="preserve">Abstract</x> Open cell‐free translation systems based on Escherichia coli cell lysates have successfully been used to produce antibodies and antibody fragments. In this study, we demonstrate the cell‐free expression of functional single‐chain antibody variable fragments (scFvs) in a eukaryotic and endotoxin‐free in vitro translation system based on Spodoptera frugiperda (Sf21) insect cell extracts. Three scFv candidates with different specificities were chosen as models. The first scFv candidate SH527‐IIA4 specifically discriminates between its phosphorylated (SMAD2‐P) and nonphosphorylated antigens (SMAD2) (where SMAD is mothers against decapentaplegic homolog 2), whereas the second scFv candidate SH527‐IIC10 recognizes both, SMAD2‐P and SMAD2. The third scFv candidate SH855‐C11 binds specifically to a linear epitope of the CXC chemokine receptor type 5. The translocation of antibody fragments into the lumen of endogenous microsomal vesicles, which are contained in the lysate, was facilitated by fusion of scFv genes to the insect cell specific signal sequence of honeybee melittin. We compared the binding capabilities of scFv fragments with and without melittin signal peptide and detected that translocated scFv fragments were highly functional, whereas scFvs synthesized in the cytosol of the cell extract showed strongly decreased binding capabilities. Additionally, we describe a cell‐free protein synthesis method for the incorporation of noncanonical amino acids into scFv molecules in eukaryotic cell lysates. We demonstrate the successful cotranslational labeling of de novo synthesized scFv molecules with fluorescent amino acids, using residue‐specific as well as site‐specific labeling.